Registry study of cardiovascular death in Sweden 2013–2019: Home as place of death and specialized palliative care are the preserve of a minority - Stina Nyblom; Joakim Öhlén; Cecilia Larsdotter; Anneli Ozanne; Carl Johan Fürst; Ragnhild Hedman (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Palliative care needs in patients with cardiovascular diseases (CVD) are expected to increase. For the planning of equitable palliative care, it is important to understand where people with CVD die. The aim was to examine trends in place of death, associated factors including utilization of specialized palliative services, and to what extent longitudinal development is influenced by national policy. Methods: A population-level registry study of place of death for adults deceased due to CVD (n = 209 671) in Sweden 2013–2019. Linear regression analysis was applied. Results: The predominant place of death was nursing home (39.1 %) and hospital (37.6 %), followed by home (22.0 %). From 2013 to 2019 home deaths increased by 2.8 % and hospital deaths decreased by 3.0 %. An overall downward trend was found for dying in hospital compared to dying at home. With variations, this trend was seen in all healthcare regions and for all CVD types, except Stockholm and cerebrovascular disease, with no significant trend. Overall, but with cross-regional variations, 2.1 % utilized specialized palliative services, while 94.2 % had potential palliative care needs. Other variables significantly influencing the trend were age and having had an unplanned healthcare visit. Conclusion: Despite a slight positive trend, only a minority of people with CVD die in their own home. Regional variations in place of death and the low and varied utilization of specialized palliative services indicate inequity in access to palliative care. Hence, the impact of current national policies is questionable and calls for strengthening through inclusion of early palliative care in specific CVD policies.